A comparative roadmap of PIWI-interacting RNAs across seven species reveals insights into de novo piRNA-precursor formation in mammals - Konstantinidou, Parthena; Loubalova, Zuzana; Ahrend, Franziska; Friman, Aleksandr; Almeida, Miguel Vasconcelos; Poulet, Axel; Horvat, Filip; Wang, Yuejun; Losert, Wolfgang; Lorenzi, Hernan; Svoboda, Petr; Miska, Eric A; et al. (Cell reports, 2024)
PIWI-interacting RNAs (piRNAs) play a crucial role in safeguarding genome integrity by silencing mobile genetic elements. From flies to humans, piRNAs originate from long single-stranded precursors encoded by genomic piRNA clusters. How piRNA clusters form to adapt to genomic invaders and evolve to maintain protection remain key outstanding questions. Here, we generate a roadmap of piRNA clusters across seven species that highlights both similarities and variations. In mammals, we identify transcriptional readthrough as a mechanism to generate piRNAs from transposon insertions (piCs) downstream of genes (DoG). Together with the well-known stress-dependent DoG transcripts, our findings suggest a molecular mechanism for the formation of piRNA clusters in response to retroviral invasion. Finally, we identify a class of dynamic piRNA clusters in humans, underscoring unique features of human germ cell biology. Our results advance the understanding of conserved principles and species-specific variations in piRNA biology and provide tools for future studies.
Keywords: piRNA; transposon; mobile genetic element; evolution; Piwi-interagující RNA; fertility; readthrough transcription; psi; PIWI; Dogs; stress; Mice; germ cell; transpozibilní elementy DNA; Animals; zvířata; Humans; Mammals; savci; Piwi-Interacting RNA; Species Specificity; CP: Molecular biology; myši; malá interferující RNA; druhová specificita; spermatogenesis; RNA, Small Interfering; lidé; DNA Transposable Elements